2017
DOI: 10.4103/2152-7806.200581
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic spine radiosurgery: Review of safety and efficacy with respect to dose and fractionation

Abstract: Background:Stereotactic body radiotherapy (SBRT) is an emerging treatment option for spinal metastases with demonstrated efficacy in the upfront, postoperative, and re-treatment settings, as well as for tumor histologies considered radioresistant. Uncertainty exists regarding the optimal dose and fractionation schedule, with single and multifraction regimens commonly utilized.Methods:A literature search of the PubMed and Medline databases was conducted to identify papers specific to spine SBRT and the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…However, more, preferably prospective, data are clearly needed to adequately address these questions. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more, preferably prospective, data are clearly needed to adequately address these questions. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, total dose and fractionation have been reported to correlate with an increased risk of fracture, with high-dose single-fraction treatment carrying the greatest risk. 27 Fracture rates approaching 40% have occurred with doses of 24 Gy in a single fraction delivered to the 100% isodose line. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Of the 366 sites treated, 96 were at levels T4 and superiorly, 270 were at levels T5 and inferiorly. To improve patient comfort, 17,18 all patients were set up with arms down at the sides or, if the target was inferior of the elbows, crossed over the chest and with the knees raised with a cushion.…”
Section: Patient Setup and Immobilizationmentioning
confidence: 99%
“…and Redmond et al., which concluded that there is currently no evidence to suggest that LC is superior with either single fraction or multifraction SBRT. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%